2016
DOI: 10.1002/per.2084
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Self–Certainty and Prosocial Development in the Transition from Late Adolescence to Emerging Adulthood

Abstract: The transition from late adolescence to emerging adulthood is a period of the life span that offers young people the possibility to consolidate their self-certainty and prosociality. Both aspects are of core importance for increasing personal and societal well-being. The purpose of this longitudinal study was twofold: (i) to examine patterns of change and stability in self-concept clarity and prosociality; and (ii) to unravel over time associations between these constructs in the transition from late adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 97 publications
(173 reference statements)
8
54
0
2
Order By: Relevance
“…Although prosocial development has long been studied, and general age-related increases have been reported from infancy through early adulthood (see Eisenberg et al 1998 ; Crocetti et al 2016 ), only a few longitudinal studies have examined changes in prosocial behavior across a broad age range in adolescence (i.e., Carlo et al 2015 ; Luengo Kanacri et al 2013 ). Yet, there is considerable evidence that several physical, cognitive, and relational changes occur during adolescence that impact social functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Although prosocial development has long been studied, and general age-related increases have been reported from infancy through early adulthood (see Eisenberg et al 1998 ; Crocetti et al 2016 ), only a few longitudinal studies have examined changes in prosocial behavior across a broad age range in adolescence (i.e., Carlo et al 2015 ; Luengo Kanacri et al 2013 ). Yet, there is considerable evidence that several physical, cognitive, and relational changes occur during adolescence that impact social functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Female adolescents were more frequently nominated as friends, and thus had the opportunity to expand their social network by accepting these friendship ties. According to literature [ 57 , 58 ] it seems, then, that studied female adolescents are more prosocial regarding these friendship levels, being able to obtain more and greater resources from the network and protecting themselves from exclusion and isolation. At the friendship level, we found that all study participants with a high SES, but males in particular, were better positioned to form ties and therefore to establish support networks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, age has been shown to be related to sustainable behavior (Wiernik, Ones, & Dilchert, 2013), materialism (Jaspers & Pieters, 2016), and selfconcept clarity (Lodi-Smith & Roberts, 2010). Similarly, gender has been shown to be related to environmentally friendly behavior (Brough, Wilkie, Ma, Isaac, & Gal, 2016) and self-concept clarity (Crocetti et al, 2016) as well. Not including these controls could therefore result in artificially inflated or lowered coefficients in our models.…”
Section: Study Overview and Empirical Strategymentioning
confidence: 99%